“If I had known, I would have applied”: poor communication, job dissatisfaction, and attrition of rural health workers in Sierra Leone - Vijay Narayan; Grace John-Stewart; George Gage; Gabrielle O’Malley (Human Resources for Health, 2018)
Abstract Background Sierra Leone’s health outcomes rank among the worst in the world. A major challenge is the shortage of primary healthcare workers (HCWs) in rural areas due to especially high rates of attrition. This study was undertaken to determine the drivers of job dissatisfaction and poor retention among Sierra Leone’s rural HCWs. Methods Interviews were conducted with 58 rural and 32 urban primary HCWs in Sierra Leone’s public health sector, complemented by key informant discussions and review of national policy documents. HCW interviews included (1) semi-structured discussion, (2) questionnaire, (3) card sort about HCW priorities, and (4) free-listing of most pressing challenges and needs. Sampling for HCW interviews was stratified purposive, emphasizing rural HCWs. Results Among 90 HCWs interviewed, 67% were dissatisfied with their jobs (71% rural vs 52% urban) and 61% intended to leave their post (75% rural vs 38% urban). While working and living conditions and remuneration were significant factors, a major reason for rural HCW disenchantment was their inability to access worker rights, benefits, and advancement opportunities. This was caused by HCWs’ lack of knowledge about human resource (HR) policies and procedures, as well as ambiguity in many policies and inequitable implementation. HCWs reported feeling neglected and marginalized and perceived a lack of transparency. These issues can be attributed to the absence of systems for regular two-way communication between the Ministry of Health and HCWs; lack of official national documents with up-to-date, clear HR policies and procedures for HCWs; pay statements that do not provide a breakdown of financial allowances and withholdings; and lack of HCW induction. Conclusions HCWs in Sierra Leone lacked accurate information about entitlements, policies, and procedures, and this was a driver of rural HCW job dissatisfaction and attrition. System-oriented, low-cost initiatives can address these underlying structural causes in Sierra Leone. These issues likely apply to other countries facing HCW retention challenges and should be considered in development of global HCW retention strategies.